Políticas públicas e gestão ambiental : um estudo do saneamento básico no município de Itiquira - MT - Vasconcelos, Monalisa Janaya Castelo da Silva (2019)
Basic sanitation is closely related to the right to health, decent housing and an ecologically balanced environment. The present research aims to carry out an analysis of the actions, projects and programs proposed in the Municipal Basic Sanitation Plan - PMSB of Itiquira-MT, evaluating popular participation in the elaboration process, considering that it is essential for the elaboration of policies as well as making a partial diagnosis of basic sanitation in the municipality. The methodology consisted of a case study, carried out through a quali-quantitative analysis, divided into 2 (two) stages. The first stage was the analysis of the Municipal Basic Sanitation Plan, where work scripts were developed to analyze the dissemination, popular participation, democratic management, investments, infrastructure and other actions, with a previous methodological script drawn up. The second stage, in turn, consisted of a partial diagnosis of sanitation in the municipality, which was carried out through the identification and location of water supply points (generation of thematic map) and discussion of test reports of water quality analysis. in the municipality. The results showed that there was significant popular participation in the elaboration of the PMSB, however, the profile of the participants must be carefully analyzed, since in the first meeting of those present, 61.84% of the individuals belonged to the School institution (Municipal and / or State) ), the vast majority of them being elementary and high school students, taken by teachers to participate, that is, there was no internal but external motivation, and the remaining majority 36.64% were individuals linked to municipal management, being civil servants public. With regard to planning and management, the municipality of Itiquira has encountered difficulties needing to improve the mechanisms of social control, advertising and democratic management, as well as implementing the proposals of the Municipal Basic Sanitation Plan - PMSB, since in the water supply sectors 87.5%, sanitary sewage 100%, urban drainage 62.50% and solid waste 75% of the proposals were not fulfilled. As for the water supply in the municipality, this is done mainly by means of tubular wells, that is, by capturing groundwater, the system consisting of 10 tubular wells and 1 monitoring well. The water quality in relation to potability is considered satisfactory for human consumption in all samples. It is concluded in this way with regard to basic sanitation in Itiquira-MT that it is of fundamental importance to promote popular participation more broadly, especially in relation to the profile of the participants, as well as to develop means to comply with the schedule established in the PMSB. And the competent bodies involved carry out the monitoring and continue the support in the implementation phase of the proposed actions.